KONSEP ETIKA KEPEDULIAN DALAM STRUKTUR KURIKULUM BERBASIS CINTA DI MI AL-ISLAH PALEMBANG - Octa Romadhona Putri; Ahmad Zainur; Muslim Gani Yasir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to deeply analyze the concept of the ethics of care within the love- based curriculum structure at MI Al-Islah Palembang. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results show that the ethics of care is not only implemented in learning but is also structured within the institutional vision, curriculum design, school culture, and character evaluation system. The integration of the values of love (mahabbah) and compassion (rahmah) serves as an epistemological foundation in building humanistic pedagogical relationships. These findings align with contemporary ethics of care theory (Noddings, 2021), social- emotional education (Schonert-Reichl, 2020), and the global humanistic education paradigm (UNESCO, 2021). This study concludes that the love-based curriculum contributes significantly to character formation, student psychological well-being, and strengthening an inclusive school culture..